A Mouse Model of Acrodermatitis Enteropathica: Loss of Intestine Zinc Transporter ZIP4 (Slc39a4) Disrupts the Stem Cell Niche and Intestine Integrity - Geiser, Jim (Public Library of Science, 2012)
Mutations in the human Zip4 gene cause acrodermatitis enteropathica, a rare, pseudo-dominant, lethal genetic disorder. We created a tamoxifen-inducible, enterocyte-specific knockout of this gene in mice which mimics this human disorder. We found that the enterocyte Zip4 gene in mice is essential throughout life, and loss-of-function of this gene rapidly leads to wasting and death unless mice are nursed or provided excess dietary zinc. An initial effect of the knockout was the reprogramming of Paneth cells, which contribute to the intestinal stem cell niche in the crypts. Labile zinc in Paneth cells was lost, followed by diminished Sox9 (sex determining region Y-box 9) and lysozyme expression, and accumulation of mucin, which is normally found in goblet cells. This was accompanied by dysplasia of the intestinal crypts and significantly diminished small intestine cell division, and attenuated mTOR1 activity in villus enterocytes, indicative of increased catabolic metabolism, and diminished protein synthesis. This was followed by disorganization of the absorptive epithelium. Elemental analyses of small intestine, liver, and pancreas from Zip4-intestine knockout mice revealed that total zinc was dramatically and rapidly decreased in these organs whereas iron, manganese, and copper slowly accumulated to high levels in the liver as the disease progressed. These studies strongly suggest that wasting and lethality in acrodermatitis enteropathica patients reflects the loss-of-function of the intestine zinc transporter ZIP4, which leads to abnormal Paneth cell gene expression, disruption of the intestinal stem cell niche, and diminished function of the intestinal mucosa. These changes, in turn, cause a switch from anabolic to catabolic metabolism and altered homeostasis of several essential metals, which, if untreated by excess dietary zinc, leads to dramatic weight loss and death.